2008
DOI: 10.1029/2007gl031589
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy as a critical factor of dust iron solubility

Abstract: [1] To understand the impact of dust deposition on ocean primary productivity, the evaluation of dust input is not sufficient, and the soluble iron supply is also needed. Measurements of iron in aerosols suggest a much higher solubility than in soil, implying substantial atmospheric processing of chemical or physical nature. Here, we have investigated the effect of the mineralogy on iron solubility. We have measured iron solubility from some minerals commonly found in dust (clay, feldspar and iron (hydr-)oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
339
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(359 citation statements)
references
References 22 publications
18
339
2
Order By: Relevance
“…Our results extend earlier research on the occurrences of iron-bearing minerals in Bodélé surface sediments and elsewhere in North Africa that aimed to establish linkages between dust mineralogy and potential environmental effects of dust (Lafon et al, , 2006Alfaro et al, 2004;Moreno et al, 2006;Mounkaila, 2006;Journet et al, 2008Journet et al, , 2104Chudnovsky et al, 2009;Lázaro et al, 2011;Maher, 2011;Shi et al, 2011;Moosmüller et al, 2012;Adetunji, 2014;Formenti et al 2014 a, b). These studies employed many methods for dust and soil mineralogy, including magnetic analyses, X-ray absorption analysis, X-ray diffraction, microscopy, elemental and isotopic chemistry combined with leaching experiments, as well spectroscopic techniques in the laboratory and applied to satellite retrievals.…”
Section: Implications For Radiative Properties and Fe Bioavailabilitysupporting
confidence: 76%
See 1 more Smart Citation
“…Our results extend earlier research on the occurrences of iron-bearing minerals in Bodélé surface sediments and elsewhere in North Africa that aimed to establish linkages between dust mineralogy and potential environmental effects of dust (Lafon et al, , 2006Alfaro et al, 2004;Moreno et al, 2006;Mounkaila, 2006;Journet et al, 2008Journet et al, , 2104Chudnovsky et al, 2009;Lázaro et al, 2011;Maher, 2011;Shi et al, 2011;Moosmüller et al, 2012;Adetunji, 2014;Formenti et al 2014 a, b). These studies employed many methods for dust and soil mineralogy, including magnetic analyses, X-ray absorption analysis, X-ray diffraction, microscopy, elemental and isotopic chemistry combined with leaching experiments, as well spectroscopic techniques in the laboratory and applied to satellite retrievals.…”
Section: Implications For Radiative Properties and Fe Bioavailabilitysupporting
confidence: 76%
“…The soluble iron fraction in mineral aerosols can vary enormously from 0.01 to 80% . Ferric oxides tend to have lower solubilities than clay minerals (Journet et al, 2008;Cwiertny et al, 2008) although the types and solubility of iron-bearing minerals carried in atmospheric dust, and the possible chemical alterations to these phases during atmospheric transport or in ocean surface waters, remain poorly understood (Shi et al, 2009(Shi et al, , 2012Nickovic et al, 2013).…”
Section: Implications For Radiative Properties and Fe Bioavailabilitymentioning
confidence: 99%
“…In this proposed mechanism, acid anion primarily reacts with the surface O-H groups followed by a proton attack yielding surface protonation. This polarizes and weakens the Fe-O bond followed by bond dissociation enabling the detachment of the Fe cation that enters into the solution (10,20). In goethite rod-shaped particles, the end of the rods that expose (021) surface planes are more reactive as a result of coordination sites with higher concentration of surface O-H groups.…”
mentioning
confidence: 99%
“…[20,21] This XANES analysis shows that iron oxyhydroxides and oxides are only part of the particulate iron in the ocean. Journet et al [22] and Schroth et al [23] have both shown that Fe-containing silicates (both clays and primary minerals) from putative atmospheric dust sources can have higher solubility than iron oxides. The abundance of clays and primary and secondary Fe-bearing silicates that we see in the water column begs for the examination of the bioavailability of these particulate iron species.…”
Section: Discussionmentioning
confidence: 99%